Cancer stem cells in solid tumors - Allan, Alison L.; SpringerLink (Online service). (Totowa, NJ Humana Press, 2011)
The ?cancer stem cell? hypothesis postulates that cancer arises from a subpopulation of tumor-initiating cells or cancer stem cells (CSCs). While the idea of cancer stem cells has been around for more than a hundred years, evidence from the fields of hematology and cancer biology has now demonstrated the critical role of stem cells in hematological malignancies and suggested that these same mechanisms are also central to the initiation, progression, and treatment of solid cancers. Clinical and experimental studies have shown that CSCs exhibit many classical properties of normal stem cells, including a high self-renewal capacity and the ability to generate heterogeneous lineages; the requirement for a specific ?niche?/microenvironment to grow; and an increased capacity for self-protection against harsh environments, toxins, and drugs.Cancer Stem Cells in Solid Tumors represents a detailed overview of cancer stem cells and their role in solid cancers. Comprised of 24 chapters, this volume will provide readers with a comprehensive understanding of this important and evolving field.
Cancer Stem Cells: Historical Perspectives and Lessons From Leukemia -- Cancer Stem Cells in Breast Cancer -- Cancer Stem Cells in Brain Cancer -- Cancer Stem Cells in Colorectal Cancer -- Cancer Stem Cells in Pancreatic Cancer -- Cancer Stem Cells in Prostate Cancer -- Cancer Stem Cells in Melanoma -- Cancer Stem Cells in Lung Cancer -- Cancer Stem Cells in Ovarian Cancer -- Cancer Stem Cells in Hepatocellular Cancer -- Cancer Stem Cells in Head and Neck Cancer -- Relationship Between Regulatory Pathways in Pluripotent Stem Cells and Human Tumors -- Influence of the Embryonic Microenvironment on Tumor Progression -- The Epithelial-to-Mesenchymal Transition and Cancer Stem Cells -- Application of Stem Cell Assays for the Characterization of Cancer Stem Cells -- Zebrafish as a Model to Study Stem Cells in Development, Disease and Cancer -- Imaging Cancer Stem Cells -- Mouse Models for Studying Normal and Cancer Stem Cells -- Cancer Stem Cells and Disease Prognosis -- Mechanisms of Radioresistance in Cancer Stem Cells -- The Role of ABC Transporters in Cancer Stem Cell Drug Resistance -- Resistance to Endocrine Therapy in Breast Cancer: Are Breast Cancer Stem Cells Implicated? -- Future Directions: Cancer Stem Cells as Therapeutic Targets -- Final Thoughts: Complexity and Controversy Surrounding the Cancer Stem Cell Paradigm.
Electronic reproduction.
Keywords: Cancer cells; Cancer -- Molecular aspects; Stem cells; Neoplastic stem cells -- Physiology; Neoplasms -- Etiology; Electronic books